Problems of the activity of canine units of the National Police in the conditions of war - V. S. Seliukov (Bulletin of Kharkiv National University of Internal Affairs)
The article highlights the main problematic issues that arise during the organization of the activities of the canine units of the National Police of Ukraine. The author's vision of the main ways and directions of solving the existing problems and peculiarities of the National Police's activities in the conditions of martial law has been formed. Emphasis is also placed on new promising directions for the use of service dogs in the police and other structures of the security and defense sector. Amendments to the regulatory framework are proposed to regulate the use of K9 units.